PENGARUH NEBULIZER, INFRARED, DAN CHEST PHYSIOTHERAPY PADA ASMA BRONCHIALE - Suci Amanati; Fitratun Najizah; Jihan Istifada (Jurnal Fisioterapi dan Rehabilitasi, 2020)
Background : Asthma Bronchiale is an obstruction of the respiratory tract due to narrowing of the airways that are reversible (narrowing can disappear by itself). But there are times when this reversible trait can be lost after getting treatment. Disorders arising from asthma bronchiale itself are shortness of breath, phlegm buildup, and spasms in the respiratory muscles. The therapy used in this case provides a nebulizer modality that helps relieve tightness and thin the sputum, infrared tries to relax reducing muscle spasm, and chest physiotherapy used to decrease breathlesness. Research Methods : This research method is experimental, research design uses case studies, and data collection techniques use Pre and Post Test. The sampling technique uses accidental sampling. Examination of breathlesness by using the respiratory rate, thorax expansion by using midline and functional activity by using modified RPE. Result : The results obtained from this study can be concluded after 4 times intervention the breathlessness was decrease, expantion of thorax was increase and there are improve of index functional. Conclution : Nebulizer, Infra red, and chest physiotherapy that give into the patient could minimaze the breathless, increase thorax expantion and inprove functional activity.